2023
DOI: 10.1002/aenm.202301784
|View full text |Cite
|
Sign up to set email alerts
|

Why Increased CdSeTe Charge Carrier Lifetimes and Radiative Efficiencies did not Result in Voltage Boost for CdTe Solar Cells

Abstract: After a focused effort over the last decade, order‐of‐magnitude improvements in doping and electro‐optical characteristics (radiative efficiency, carrier lifetime, and passivation) have been reported for polycrystalline CdSeTe solar cells. Surprisingly, this did not result in higher solar cell voltages regardless of device contacting layers, absorber grading profiles, and other changes in device architecture. From detailed evaluation of radiative emission and carrier dynamics in CdSeTe heterostructures and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…[ 1,2 ] However, realizing high open‐circuit voltage ( V OC ) remains a considerable challenge. [ 3–7 ] Efficient power conversion in solar cells depends on the generation, transport, and collection of charge carriers, processes which are sensitive to the absorber layer's characteristics and to the device interfaces. [ 8–18 ] Charge carrier dynamics within this framework are described by the drift‐diffusion equation, [ 19 ] which for electrons in one dimension is:n(x,t)t=D2n(x,t)x2+μEn(x,t)t+G(x,t)R(n(x,t))$$\frac{\partial n \left(\right.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1,2 ] However, realizing high open‐circuit voltage ( V OC ) remains a considerable challenge. [ 3–7 ] Efficient power conversion in solar cells depends on the generation, transport, and collection of charge carriers, processes which are sensitive to the absorber layer's characteristics and to the device interfaces. [ 8–18 ] Charge carrier dynamics within this framework are described by the drift‐diffusion equation, [ 19 ] which for electrons in one dimension is:n(x,t)t=D2n(x,t)x2+μEn(x,t)t+G(x,t)R(n(x,t))$$\frac{\partial n \left(\right.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, τ rad , τ srh , and τ eff represent the radiative, nonradiative, and effective carrier lifetimes, and k denotes the radiative recombination coefficient. Equation (3) shows that the shortest lifetime at any given carrier concentration dominates the recombination. Figure 1 illustrates how the effective carrier lifetime τ eff varies with carrier concentration n. At low n, τ rad is long as it is inversely proportional to n; thus, the nonradiative recombination τ srh dominates in this region, which is governed by defect density, capture rate, and surface recombination velocity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial impact of the back contact barrier reduction may outweigh any detrimentally reduced τ 2 lifetime. A recent study demonstrated that in undoped CdSeTe, high τ 2 lifetimes might correspond to trapping/detrapping mechanisms that not only increase τ 2 but also impart a lower hole mobility on the absorber, increasing the sensitivity of V OC to the magnitude of any back contact barriers . Despite the improved V OC with continuous gold contacts, AlGaO x cannot be used directly with CFL-templated nanogrids due to the high series resistance stemming from the low in-plane conductivity of the AlGaO x layer.…”
mentioning
confidence: 99%
“…A recent study demonstrated that in undoped CdSeTe, high τ 2 lifetimes might correspond to trapping/detrapping mechanisms that not only increase τ 2 but also impart a lower hole mobility on the absorber, increasing the sensitivity of V OC to the magnitude of any back contact barriers. 23 Despite the improved V OC with continuous gold contacts, AlGaO x cannot be used directly with CFL-templated nanogrids due to the high series resistance stemming from the low in-plane conductivity of the AlGaO x layer. Au nanogrids deposited on this AlGaO x layer resulted in similarly improved V OC but a drastic reduction in fill-factor (70.2% to 41.4%) due to the introduction of additional series resistance ( Figure 4 a).…”
mentioning
confidence: 99%